Reorientasi Arah Dakwah Dalam Bingkai Kebhinekaan (Antara Tantangan dan Harapan dakwah di Masa Pandemi Covid-19) - Abdul Wahid (RETORIKA : Jurnal Kajian Komunikasi dan Penyiaran Islam, 2021)
This paper contains about the reorientation of the direction of da'wah in the frame of diversity or pluralism. Da'wah as a social engineering cannot escape from the various realities and dynamics of society, including currently there is a pandemic problem that is engulfing the world which until now has been counted for approximately two world years. The result is really very powerful where all the order of human life can change drastically, both in terms of health but also economic, social, educational and religious issues. Besides the problem of the pandemic, there is the issue of diversity or pluralism which is an important part and must be faced by the da'i in the implementation of da'wah. For this reason, the reorientation of the current and future direction of da'wah must be considered immediately so that the teachings of Islam that are transformed into the ummah are truly accommodating, especially in addressing the issue of the Covid-19 pandemic and diversity.